Case report: Spontaneous abortion of monoamniotic twins at the third trimester of pregnancy in Camelus dromedarius - Hossein, Mohammad Shamim; Son, Young-Bum; Jeong, Yeon Ik; Kang, Mina; Lee, Seejin; Tinson, Alex; Hwang, Woo Suk (Frontiers in Veterinary Science, 2023)
Monoamniotic twins develop when a blastocyst spontaneously splits its progenitor cells, and each group of progenitor cells independently grows to become an individual. It is the rarest type of twin pregnancy and usually has significant developmental or congenital abnormalities, a higher rate of abortion, perinatal morbidity, and mortality. There is no information regarding monoamniotic twins in livestock species. Here, we reported a spontaneous abortion of monoamniotic twins in a dromedary camel at 278 days of gestation. Gonadorelin acetate (100 μg) was injected intramuscularly to induce ovulation in the recipient. A 7 days-old embryo produced by somatic cell nuclear transfer was transferred transcervically to the recipient. Early pregnancy was confirmed by an elevated level of serum progesterone followed by ultrasonography at 22 and 44 days after embryo transfer. A single sac was observed on 22 days while twins were evident 44 days after embryo transfer. Pregnancy was periodically monitored by the tail-up phenomenon. A ruptured fetal sac was observed on the ground having two fetuses. On autopsy, full-grown fetuses were found. Their bodies were separated. There was no congenital anomaly or any malformation in the fetuses. According to the reported chronology in human twins, we hypothesized that the blastocyst splitted before 13 days as it was monoamniotic and not conjoined. If the embryo splits within 4 to 8 days, it develops two amniotic sacs, and splitting after 13 days develops conjoined fetuses. To the authors’ knowledge, this is the first reported case of monoamniotic twin abortion in dromedary camels. This report will increase awareness among practicing veterinarians and camel breeders about twin abortions.